FCA!35 [videorecording (DVD)] : Frampton comes alive - Frampton, Peter (Eagle Vision, 2012)
In 2011 and 2012, Peter Frampton toured in celebration of the 35th anniversary of his landmark live album, "Frampton comes alive".